Inventory of Electronic Waste (E-Waste) and Residues in Junkshops: A Step Towards Residual Waste Management - Ventabal, Rachel Alexis S.; Cruz, Zia May S.; Santos, Jasper F.; Basilio, Eleonor R. (Three E Science Institute, 2024)
The improper management of Waste Electrical and Electronic Equipment (WEEE) constitutes a critical global environmental challenge, with a significant proportion of e-waste ending up in landfills, posing substantial ecological and health risks. In the Philippines, particularly in areas like Marilao, many individuals rely on the recycling of e-waste for their livelihoods, primarily through junkshops and informal recycling networks. Despite providing economic benefits, these practices often result in substantial residual waste, exacerbating landfill overflow and environmental degradation. This study aims to establish a detailed e-waste inventory and propose practical strategies for improving residual waste management. This research used a mixed-method approach to collect data via surveys, interviews, and direct observations at selected junkshops in Marilao. The findings enabled a comprehensive categorization of e-waste based on economic value, highlighting